Pengaruh Kompensasi Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT Bumi Berkah Boga Bekasi Barat - Corry Adrizka Chairunisa; Andri Priadi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of compensation and physical work environment on employee performance at PT Bumi Berkah Boga West Bekasi The method used in this study is with quantitative descriptive methods. The population in this study is employees of PT Bumi Berkah Boga which amounts to 55 employees and the sample in this study uses saturated samples, which uses the entire population as a sample. with an error rate of 5%. Data collection techniques in this study used questionnaires. Data analysis techniques with simple and multiple linear regression. The results showed that partial compensation (X1) had a positive effect on the performance of cariawan (Y) with a coefficient of 19.3% and Tcalculate (4.482>2.00665). The work environment (x2) has a positive effect on the performance of Y employees with a coefficient of determination of 3.3% tcalculate (-2.849<2.00665). Employee performance (Y), correlation coefficient Compensation (X1) and work environment (X2) have a moderate level of influence or relationship on employee performance with a coefficient of determination of 30.2% and Fcalculate (11.271>3.17). Based on the results of calculations that have been carried out, it can be interpreted that H1, H2 and H3 are accepted, this shows that it is proven that there is an influence of compensation and physical work environment on employee performance both partially and simultaneously.